Foraging Behavior and Colony Cycle of Agelaia vicina (Hymenoptera: Vespidae; Epiponini) - Oliveira, Otavio A. L. de [UNESP]; Noll, Fernando B. [UNESP]; Wenzel, John W. (Pensoft Publishers, 2010)
The neotropical Age lain vicina has the largest nest built among social wasps, yet little is known about nest construction, growth and structure. In this work, the development of two nests of A. vicina was followed. Studies were done through analysis of images to estimate the growth of nests. The material collected below the nests was examined to estimate colony productivity. Nests were collected to analyze their architecture and structure. Colony cycle was similar in the two colonies. Colonies increase in size throughout the dry season and into the rainy season, with a sudden drop in production at the end of the rainy season. The colonies doubled in size in about six months.